2017
DOI: 10.1002/acr.23242
|View full text |Cite
|
Sign up to set email alerts
|

Cost‐Utility Analysis of High Molecular Weight Hyaluronic Acid for Knee Osteoarthritis in Everyday Clinical Care in Patients at a Working Age: An Economic Evaluation of a Randomized Clinical Trial

Abstract: Objective. Knee osteoarthritis (OA) is associated with high medical costs and especially with high productivity costs, in particular in patients in their working years. High molecular weight (HMW) hyaluronic acid (HA) is an alternative treatment for nonsteroidal antiinflammatory drugs, which are known for their serious side-effects. The cost-utility of intraarticular HMW-HA treatment in these patients is unknown, however, and was assessed in this study. Methods. Secondary care patients ages 18-65 years with kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 43 publications
0
28
0
1
Order By: Relevance
“…The cost-effectiveness analysis was in favour of VS. 56 Another study conducted in individuals of productive age (between 18 and 65 years old) concluded that the addition of high-molecular weight hyaluronic acid to the routine OA treatment is cost-effective. 57 Finally, a study carried out with the top 5 brands of hyaluronic acid on the American market concluded that viscosupplementation with any of was more cost-effective compared to routine treatment. Thus, the panel was strongly in agreement that viscosupplementation generates cost reductions for the supplementary health system and is a cost-effective procedure.…”
Section: Resultsmentioning
confidence: 99%
“…The cost-effectiveness analysis was in favour of VS. 56 Another study conducted in individuals of productive age (between 18 and 65 years old) concluded that the addition of high-molecular weight hyaluronic acid to the routine OA treatment is cost-effective. 57 Finally, a study carried out with the top 5 brands of hyaluronic acid on the American market concluded that viscosupplementation with any of was more cost-effective compared to routine treatment. Thus, the panel was strongly in agreement that viscosupplementation generates cost reductions for the supplementary health system and is a cost-effective procedure.…”
Section: Resultsmentioning
confidence: 99%
“…Previous literature has demonstrated the cost-benefits of IA-HA use in comparison to other treatment options; however, this study utilizes a real-world evidence approach to evaluate all recorded health KOA-related costs rather than employing modeling methods to derive costs. [15][16][17][18][19][20][21] The direct evaluation of KOA-related costs within a national database provides a more representative assessment of the costs associated with KOA and how those costs may differ when IA-HA is included in the disease management paradigm. From a value-perspective, the potential cost savings seen when IA-HA is utilized should be taken into consideration along with the efficacy and safety evidence for this treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In line with OARSI and ESCEO guidelines the NOV considers HA a secondary course of treatment for knee OA, but is not recommended for individuals with hip or polyarticular OA [ 2 , 4 ]. A recent study of Hermans et al showed that intra-articular HA injections had a good effect for knee OA in Dutch patients of working age and suggested that the use of HA is cost-effective for the Dutch health care situation [ 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%